Molar and incisor hypomineralization: Challenge from diagnosis to therapeutic possibilities (Research, Society and Development, 2023)
The objective of the present study is to discuss, through a narrative literature review, the characteristics of MIH in order to demystify the diagnosis, treatment and prognosis of the affected dental elements. This is a narrative review of qualitative literature. To develop the study, searches were carried out for articles in the main health sciences journals, such as: PubMed, LILACS and Embase. The search filters were applied to studies published between 2019 and 2023. The inclusion criteria involved bibliographic reviews, cohort, cross-sectional, case-control studies, applied research and pilot studies. At the same time, exclusion criteria were established for books, book chapters, letters to the author, abstracts of annals, theses, dissertations, opinion articles and those studies that did not corroborate the proposed objective established for this research. The selected studies totaled 29 articles and were subdivided in order to develop a brief bibliographic review, thus the foundation allowed the development of subtopics: definition, etiology, diagnosis and treatment. It is concluded that molar-incisor hypomineralization (MIH) is a complex dental condition that affects permanent molars and incisors, presenting challenges in diagnosis, treatment and prognosis. Its etiology is multifactorial, and includes genetic, environmental and perinatal factors, resulting in variations in prevalence in different populations. Diagnosis requires a detailed examination due to its similarity to other dental conditions, while treatment ranges from preventative measures to invasive restorations, tailored to the patient's needs.